2011
DOI: 10.2319/041911-274.1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of third-molar agenesis in an orthodontic patient population with different skeletal malocclusions

Abstract: Objective: To examine the relationship between third-molar agenesis and different skeletal malocclusion patterns. Materials and Methods: Pretreatment records of 1046 orthodontic patients (aged 13-17 years; mean age, 14.07 6 1.27) were used. Third-molar agenesis was calculated with respect to genders, number of missing teeth, jaws, and skeletal malocclusion patterns. The Pearson chi-square test was performed to determine potential differences. Results: Among the 1046 subjects, 237 subjects were diagnosed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
43
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 20 publications
15
43
2
2
Order By: Relevance
“…The 2 studies that investigated the association of third molar agenesis, and the vertical skeletal dimensions display conflicting results. Celikoglu and Kamak (2012) reported that agenesis of the third molar does not depend on vertical patterns of the skeletal malocclusions (6). There was similar prevalence rate of third molar agenesis among the hyper-divergent (24.5%), normal (23.8%), and hypodivergent (19.2%) groups.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The 2 studies that investigated the association of third molar agenesis, and the vertical skeletal dimensions display conflicting results. Celikoglu and Kamak (2012) reported that agenesis of the third molar does not depend on vertical patterns of the skeletal malocclusions (6). There was similar prevalence rate of third molar agenesis among the hyper-divergent (24.5%), normal (23.8%), and hypodivergent (19.2%) groups.…”
Section: Discussionsupporting
confidence: 49%
“…Third molar hypodontia seems to follow a similar pattern. It was shown that third molar agenesis was seen less in patients with skeletal Class II, and was most common in Class III skeletal relationship (6,16). Celikoglu and Kamak (2012) reported that the prevalence of third molar agenesis in those with a Class III malocclusion (28.4%) was significantly higher than in those with Class I (20.3%), and Class II (19.9%) malocclusion (6).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Furthermore, we observed higher frequency of M3 agenesis in maxilla (61.5%) compared to mandible (11.5%) which is similar to the study by Celikoglu and Kamak, 9 Kazanci, 3 Afzal et al 20 and Mok & Ho. 7 In addition, there was a significant difference in the occurrence of M3 agenesis between upper and lower jaw (p=0.001).…”
Section: Resultssupporting
confidence: 90%
“…Few studies showed that hypodontia patients have higher tendency towards skeletal Class III pattern 23,24 followed by Class I. 9 This study also found the similar results with skeletal Class III patients having highest occurrence of M3 agenesis followed by skeletal Class I. In consistent with the study done by Celikoglu et al, 25 present study showed that the skeletal Class II malocclusion were less affected by M3 agenesis compared to other groups.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation